Molecular recognition with boronic acids-applications in chemical biology. - Whyte,GF; Vilar,R; Woscholski,R (J Chem Biol, 2013)
Small molecules have long been used for the selective recognition of a wide range of analytes. The ability of these chemical receptors to recognise and bind to specific targets mimics certain biological processes (such as protein-substrate interactions) and has therefore attracted recent interest. Due to the abundance of biological molecules possessing polyhydroxy motifs, boronic acids-which form five-membered boronate esters with diols-have become increasingly popular in the synthesis of small chemical receptors. Their targets include biological materials and natural products including phosphatidylinositol bisphosphate, saccharides and polysaccharides, nucleic acids, metal ions and the neurotransmitter dopamine. This review will focus on the many ways in which small chemical receptors based on boronic acids have been used as biochemical tools for various purposes, including sensing and detection of analytes, interference in signalling pathways, enzyme inhibition and cell delivery systems. The most recent developments in each area will be highlighted.